PERAN PARA PIHAK DALAM HUBUNGAN KERJA PEKERJA OUTSOURCING YANG MENJADIKAN HUBUNGAN KERJA HARMONIS - Siti Hanah; Nur Asmilia (EkoPreneur, 2019)
This paper discusses "Employment work relations outsourcing", is one important factor in running the company wheels. This paper examines the work relations of HR very influential on company performance which ultimately inline to the company's revenue and profit (margin). In this paper the authors use the concept of employment relations OUTSOURCING workers are employed, THROUGH "SERVICE / JOB CONTRACT" or "MANPOWER SUPPLY / BODY SHOP, to examine in depth and identify both in terms of law, basic conditions, impacts both for workers and companies, rights and rights the obligations of each party, termination of employment. Keywords: Employee relations with harmonious employers